(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to determine the career preferences of medical students and to identify differences between male and female medical students. These results are helpful in understanding current thinking of medical students and provision of health for all and designing future health policies of the country. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at Islamic International Medical College Trust (IIMCT), Rawalpindi from January 2014 to April 2014. Materials and Methods: This study was performed at Islamic International Medical College Trust (IIMCT) including 100 students from the first year and 100 students of final year MBBS. The College is a private medical school located in Rawalpindi. Inclusion criteria: All students of 1st year and final year MBBS. Exclusion criteria: Incompletely filled questionnaire excluded from the study Results: Socio demographic: Response rate was 92.5% with 185 questionnaires out of 200 completed and returned. Mean age of the respondents was 21.5 years, ranging between 20 and 25 years. One hundred eleven (111) (60 %) respondents came from major cities, eighteen (18) (9.7%) lived abroad, whereas 21 (11.4%) came from rural or semi-urban areas of Pakistan. In our sample a large proportion of the students were females. Location of practice: Most of the students preferring to settle in an urban setting. Majority of students want to do post graduation, very few opted for general practice and one third thinking of abroad for post graduation and only a few want to locate their practice in rural areas. Conclusion: Medical graduates prefer clinical specializations over general practice as career. Strategies need to be planned by public and private sector and implemented to stop the brain drain and retain the medical personnel to provide effective health care for all including rural areas.